Health-related quality of life and influencing factors in parents of children with congenital heart disease: a systematic review and meta-analysis - Wang, Yu; Ma, Fang; Yang, Jingran; Zhang, Yimei; Zhou, Min; Bai, Yangjuan; Elmobasher, Majd; Chen, Zhisong (Frontiers in Public Health, 2025)
IntroductionParents of children with congenital heart disease (CHD) have been described as ‘hidden patients,’ which negatively impacts their health-related quality of life (HRQoL). The extent of HRQoL impairment among parents of children with CHD and its contributing factors remain controversial. This systematic review and meta-analysis aimed to systematically examine the HRQoL in parents of children with CHD and sought to determine the influencing factors.MethodsA comprehensive search for articles was performed via CINAHL, Embase, PsycINFO, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical (Sinomed), Weipu (VIP), and Wanfang databases from the establishment of the database to September 30, 2024. Cross-sectional, cohort and case–control studies, evaluating the HRQoL or influencing factors for parents of children with CHD were identified and collected.ResultsOf the 4,013 studies identified, one cohort study and 22 cross-sectional studies comprising 3,681 parents of children with CHD were included. Pooled results indicated that in each domain of the Short Form-36 Health Survey (SF-36), the HRQoL scores for general health (SMD, −0.58; 95% CI, −0.79, −0.37; p < 0.001), role difficulty due to emotional problems (SMD, −0.79; 95% CI, −1.00, −0.58; p < 0.001), role difficulty due to physical problems (SMD, −0.31; 95% CI, −0.52, −0.11; p = 0.003), and social function domains (SMD, −0.53; 95% CI, −0.74, −0.33; p < 0.001) in mothers of children with CHD were lower than those in mothers of healthy children. There was a negative correlation between negative coping and HRQoL in parents of children with CHD (r = −0.07, p = 0.003).ConclusionCompared with the general population, mothers of children with CHD have lower social function and general health and more role difficulty due to emotional and physical problems. Meanwhile, negative coping is a potential influencing factor in the HRQoL of parents of children with CHD. Notably, SF-36 scores did not significantly differ in mental health, physical function, vitality, and pain domains between mothers of children with CHD and the general population, from our result was that, regardless of the mental or physical health scores, and even in the total HRQoL scores, there were no statistically significant differences between fathers and mothers who had a CHD child.